APPLICATION OF GINGER ESSENTIAL OIL IN THE FOOD SECTOR - Iqbal, Mochammad (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2022)
This study aims to determine the usage of spice essential oils, specifically ginger, in the food sector. This study is a literature study. The source of the article writing library were taken from Google Scholar and www.scimagojr.com with relevant study. According to the findings, essential spice oils, especially ginger, can be used as seasonings in the food sector which can extend the shelf life and enhance the taste of a product. This is supported by the chemical nature of ginger essential oil, which contains compounds. Therefore, food additives can be added to the food manufacturing process. Since the main principle of adding food additives is to prevent the growth, oxidation and unwanted chemical changes of bacteria, so that food looks good as well as its tastes, hence food can be consumed safely. Keywords: Ginger Essential Oil, Food Sector, Shelf Life